Ontogenes and the Problem of Speciation - F Chadov Boris; Chadova E.V.; Fedorova N.B (Journal of Evolutionary Science, 2019)
The existing hypotheses on speciation rely on Mendelian genes and mutations in them. However, genome-wide sequencing demonstrates that the Mendelian genes account less than one-tenth of the entire genome DNA. This means that a greater part of the genome has not yet been subject to large-scale evolutionary consideration. This paper deals with the conditional mutations in drosophila, which are mutations of the genes belonging to a special category (ontogenes) controlling the program of individual development. The ontogenes presumably reside in the DNA of intergenic spaces and introns. Conditional mutations display a number of properties absent in the mutations of Mendelian genes. These specific properties allow three key problems in speciation to be solved: (1) the possibility of emergence of new traits as a result of sequential mutagenesis; (2) selection of mutants; and (3) establishment of isolation. We have shown that (1) the mutations in ontogenes are able to form new multigenic regulatory blocks that escape selection during their creation; (2) mutations in ontogenes allow for existence of constantly acting zygotic selection, which is by no means less important for speciation than Darwinian selection; and (3) owing to their conditionally lethal effect, the mutations in ontogenes are able to create biological isolation barrier. This gives the grounds for assuming that the emergence of mutations in ontogenes is a necessary condition for speciation.
Keywords: speciation